2007
DOI: 10.1097/01.hp.0000248146.90949.0d
|View full text |Cite
|
Sign up to set email alerts
|

CORNEAL ENDOTHELIAL INJURY THRESHOLDS FOR EXPOSURES TO 1.54 ??m RADIATION

Abstract: The endothelial injury threshold was determined in rabbit for an 11-s exposure to 1.54 micro m radiation from an Erbium fiber laser. The beam was Gaussian with a 1/e diameter of 7 mm. Cell damage was detected with a wet staining technique. The threshold dose for these conditions is 4.4 x 10(5) J m(-2) (44 J cm) and is only 9% greater than the threshold for epithelial damage for the same exposure conditions. Exposures just above the threshold caused substantial endothelial damage, including loss of cells. The c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…With the increasing use of infrared lasers in diverse fields, including military, medicine, and industry, concerns have been raised about the potential injuries of infrared lasers. Corneal damage thresholds at various wavelengths have been reported, including 1.319, 9,10 1.54, [11][12][13] 2.02, [14][15][16] 3.74, 17 and 10.6 μm. 18 Although existing studies mainly reported corneal damage characteristics at 0, 24, and 48 h postexposure, the pathophysiological process of corneal wound healing was not investigated thoroughly.…”
Section: Introductionmentioning
confidence: 99%
“…With the increasing use of infrared lasers in diverse fields, including military, medicine, and industry, concerns have been raised about the potential injuries of infrared lasers. Corneal damage thresholds at various wavelengths have been reported, including 1.319, 9,10 1.54, [11][12][13] 2.02, [14][15][16] 3.74, 17 and 10.6 μm. 18 Although existing studies mainly reported corneal damage characteristics at 0, 24, and 48 h postexposure, the pathophysiological process of corneal wound healing was not investigated thoroughly.…”
Section: Introductionmentioning
confidence: 99%